Mudanças na relevância da informação contábil para o mercado de capitais nos últimos 20 anos: evidências do Brasil - Queiroz, Igor Toledo de (2018)
The present paper aimed to provide evidences about the value relevance of accounting information to capital markets through the years. As specific objectives, the research aimed to investigate what is the trend around the value relevance, and if, on average, the adoption of IFRS made the information more value relevant. To the former investigation a cross section regression was adopted, and to the later, a pooled data regression. This paper adopts the classic Ohlson (1995) modelo, that regresses price on earnings per share and book value per share, with the addition of control variables accordingly to Balahandran and Mohanram (2011): industry and ocurrence of loss. Concerning the trend, the evidences indicate that there was a trend of loss of relevance before the adoption of IFRS, and a trend of increase of relevante after. The pooled data regression provided a higher R 2 after the adoption of the IFRS and a higher inclination coefficient for earnings and book value, which suggest that the adoption increased the value relevance of accounting information. This evidence is in general, in the same direction as the presented literatature. Moreover, the research observed contrary evidences to works that investigate relevance over time: in Brazil, book value per share has a declining trend while earnings per share has a increasing trend. These results should be observed with caution, since some national researches indicate that the increase in relevance is sometimes also associated with the governance practices adopted by firms.